MANAGEMENT OF FINANCIAL AND ECONOMIC SECURITY OF INNOVATION-ORIENTED SOCIO-ECONOMIC SYSTEMS - NYZHNYK, Oleh; NYZHNYK, Iryna; LYSAK, Viktor (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The modern paradigm of financial and economic security management of innovation-oriented socio-economic systems should be based on guidelines for action and management decisions aimed at ensuring and improving the level of financial and economic security. The authors consider the management of financial and economic security of innovation-oriented socio-economic systems in terms of complexity and individuality of the choice of components. The article identifies the levels of a comprehensive system of financial and economic security of higher education institutions as socio-economic organizations (institutions). The authors propose to manage the financial and economic security at both the tactical and strategic levels. This study identifies the main functions, principles and criteria of the regulatory and planned level of financial and economic security of higher education institutions and puts forward a modern concept of security of innovation-oriented socio-economic systems.The article proves that the management of financial and economic security of innovation-oriented socio-economic systems has a complex structure, which includes: goals, principles, actors, objects, tasks, functions, measures, levers and tools. Each of these components has its own characteristics, performance requirements, relationships. Innovation-oriented socio-economic systems for their safe operation must independently develop and adhere to a defined management strategy, the stages of which are described for their practical use in the management of financial and economic security. To ensure and increase the level of financial and economic security of innovation-oriented socio-economic systems, the following methods should be developed: technical, financial, informational, legal, personnel, intellectual and innovative. The authors of the article include the following principles of financial and economic security of innovation-oriented socio-economic systems: timeliness, complexity, system, legality, activity, specialization, coordination and interaction, centralization, management flexibility and sufficiency in management. These principles are included in the general structure of the management system of financial and economic security of non-productive entities.
Keywords: management; financial and economic security; innovation-oriented systems; institutions of higher education